Dwelling : a novel - Kivel, Emily Hunt, 1992- (Farrar, Straus and Giroux, 2025)
"A dazzling, surrealist debut novel about a young woman's quest for house and home-from New York to the Texas hinterlands and, maybe, back again."-- Provided by publisher.